Potret Keberadaan Kesenian Wayang Kulit di Bekasi: Wayang Kulit Akulturasi (Periode Tahun 1970-2015) - Dalila Kusuma Wardani; Didin Saripudin (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2021)
This article aims to describe the development of wayang kulit in Bekasi in 1970-2015. Broadly speaking, the main problem studied in this article is about "How is the existence of wayang kulit in Bekasi in the midst of the rapid pace of globalization in 1970-2015?". The author uses historical methods consisting of four steps: heuristics, source criticism, interpretation, and historiography. Based on the results of research in its development, wayang kulit in Bekasi experienced dynamics in the span of 1970-2015. In the 1970s this art is in great demand by the public, it can be seen from the intensity of the performance is very dense. But entering 2015 the intensity of wayang kulit performances in Bekasi is decreasing. This indicates that the Betawi puppet was demoted by Betawi ethnic community it self and the society in general. Globalization is one of the factors that cause a decrease in public interest in traditional arts.